Response to antiretroviral therapy undergone by HIV/AIDS patients - Yasin, Nanang Munif; Maranty, Hesaji; Ningsih, Wahyu Roossi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
HIV/AIDS, with new cases thereof coming up year after year, is a fastgrowing disease. In order to inhibit HIV replication, ARV is administered to HIV/AIDS patients throughout his life-time. Continuous monitoring for the detection of its desired result ought to be conducted. This study is aimed to find out the response of the ARV therapy undergone by the HIV/AIDS patients hospitalized in a teaching hospital in Yogyakarta. Descriptive non-experimental design was used for the study. The data were obtained retrospectively from medical records of 71 patients who met the inclusion and exclusion criteria. The data were analyzed descriptively.The research findings indicated that of the first-line ARV therapy, zidovudine+lamivudine+nevirapine (AZT+3TC+NVP) was mostly used (61.97%). It was found that all of the ARV types used were in accordance with the National Therapy Antiretroviral Guidelines (2007) from Health Ministry Department, Indonesia. As observed further, 61 (92.80%), 40 (85.00%), and 20 (85.00%) patients had their CD4 increased; 66 (72.72%), 44 (75.00%), 24 (79.17%) had gained weight; and 71 (100%), 55 (100%), and 31 (96.77%) had survived the disease after 6, 12, and 24 months undergoing ARV therapy. However, the increase in CD4 after six-month therapy was not always attended by the increase in weight. To conclude, this phenomenon indicated good immune and clinical responses.Key words: HIV/AIDS, antiretroviral, therapy response, CD4count, hospital